An assessment of green practices in a hotel supply chain: A study of UAE hotels. (September 2017) - Al-Aomar, Raid; Hussain, Matloub
Abstract: The purpose of this paper is to develop a framework for green assessment across a hotel supply chain. The proposed framework was derived from the theory of "value creation" with a focus on green awareness, green know-how, and green implementation. These aspects are further explored using a structured research method and specific research questions. The study was conducted in selected hotels in the United Arab Emirates (UAE). The study has identified the currently used green practices across the supply chains of the surveyed hotels. Study results have confirmed the familiarity of UAE hotels with green practices and the awareness of green value. However, there was a gap in the green know-how in terms of the effective implementation of green techniques across the supply chain and the impacts of the adopted green practices. The study has also identified the obstacles of adopting green practices across the hotel supply chain. Literature indicates a growing awareness of adopting green practices in the service sector in general and in the hospitality industry in particular. However, despite the viability of the topic, it appears that comprehensive theoretical and analytical frameworks for assessing green practices in hotel supply chains are still underdeveloped. Thus, the proposed framework can be subsequently used by practitioners and researchers in conceptualization and assessment of green practices across hotel supply chains in the UAE and the region. Results also provide insight and guidance for adopting green practices across the supply chains of hotels globally.